SCHOOL OF CRIME PROCESS FOR RESIDIVIST PRISONERS - Maryadi, Muhammad; Rahayu, Mulyani (Universitas Nusa Cendana, 2025)
Crime is a phenomenon that cannot be avoided and occurs very often in society. Crime can happen to someone regardless of the victim's background, so it can be said that crime cannot be avoided in society and can cause anxiety and a sense of insecurity for Indonesian society. The aim of this research is to understand the school of crime process of recidivist prisoners in this case study (Case Study of the Kalianda Class IIA Penitentiary). After going through the stages of the judicial process such as investigation, trial and determination of punishment, the perpetrator of the crime will be directed to serve his sentence in a correctional institution. Prisoners in correctional institutions receive personality and independence development. The coaching program was not successful because of the large number of prisoners. As a result, there is a School of Crime within the